A German officer in occupied Paris : the war journals, 1941-1945 : including "Notes from the Caucasus" and "Kirchhorst Diaries" - Jünger, Ernst, 1895-1998 (European perspectives., 2019)
"Over an amazing 80-year career as a writer, Ernst Jünger (1895-1998) fought in WWI, became a leading writer of "soldierly nationalism" in the 1920s, and produced possibly the only anti-Nazi novel during the Third Reich, On the Marble Cliffs. Jünger's seeming moral ambiguities have made him the subject of much controversy in his home country. He has long been the subject of a series of highly charged debates about his work, and his presentation with the Goethe Prize (Germany's highest literary honor) in 1982 revived an old charge that Jünger had helped pave the way for fascism. The French, however, regard him as Germany's greatest twentieth-century author. Jünger's war diaries are important historical documents. He rejoined the army in 1941 and was sent to Paris, where he was in a unique position to observe the German occupation of France from the point of view of an occupier, but one who was not blinded by Nazi ideology. The First Paris Diary begins in 1941, when Jünger began his war duties as a mail censor of the occupying regime, and ends in October of 1942, as he leaves Paris to travel to the Eastern Front. Through his high-level contacts, Jünger was aware of the situation on the Eastern front and the atrocities being committed there. He was also a member of a secret circle of aristocratic officers, led by Rommel, who opposed Hitler's conduct of the war and were conspiring to arrest him in France in 1944 and turn him over to allies in exchange for lenient armistice conditions. In addition to descriptions of his official duties, the diaries describe Jünger's wanderings through Parisian bookshops and cafes, his conversations at salons with French intellectuals, and his reflections on books and nature (he was a trained biologist)"--